Stationary target localization and circumnavigation by a non‐holonomic differentially driven mobile robot: Algorithms and experiments. (18th October 2020) - Wang, Lei; Zou, Yao; Meng, Ziyang
Summary: This article addresses a surveillance problem where the goal is to achieve a circular motion around a target by a non‐holonomic differentially driven mobile robot. The available information for the mobile robot includes its own position, velocity with respect to the inertial frame, and the bearing angle of the target in its body frame. Since the target position is unavailable, an estimator is first proposed to localize it. Then a two‐step controller is given to drive the mobile robot to move onto a circular trajectory with a desired radius around it. It is shown that the proposed algorithm guarantees the convergence of the estimation error to a small neighborhood of zero and the motion of the robot to a small neighborhood of a designed radius. The performance of the proposed algorithm is first verified by simulations. Then, several experiments on a differentially driven mobile robot, Pioneer 3‐DX, are presented to further validate the proposed algorithm.